Information management and control systems in the port community: insights and challenges from regulations. (2016) - Vaio, Assunta Di; Varriale, Luisa
This paper aims at investigating the role of information management and control systems in the inter-organisational relationships between the Port Authority (PA) and port users, adopting an information technology platform, as the Port Community Systems (PCSs). We focus on the effects of the PCSs implementation on the information management, and control systems used to support the decision making of the Port Authorities (PAs). We conduct a literature review on regulations and digitalisation of operating processes in the seaports, and the related information management. Through the case study methodology, we used semi-structured interviews to port users and PA in an Italian seaport. Drawing from perspectives of the Balanced Scorecard (BSC), we identify some key performance indicators (KPIs) addressed to measure and control the information and data flows concerning the processes within the inter-organisational relationships in the port community. The study provides interesting theoretical and managerial implications, especially highlighting the positive effects of PCSs.